Investigating the effect of depression, stress, and attachment style on leftward cradling bias. - McGrath, Margaret J (Department of Psychology, 2014)
The majority of women cradle infants to the left of their midline ? this phenomenon is known as leftward cradling bias. The right hemisphere's specialization for emotional processing is believed to explain the bias as it would facilitate emotional communication between the parent and child. Thus, it is of scientific and clinical interest to investigate the disruptors of leftward cradling bias. This study examined three possible disruptors of leftward cradling: stress, depression and attachment style. In total, after exclusion criteria were applied, 468 female students participated. Information was collected over the internet via surveys and using an imaginary cradling task, to facilitate obtaining a large sample. A hierarchical regression model was developed to concurrently examine the effect of depression, stress, and attachment style on leftward cradling bias. The hierarchical regression model was not statistically significant;; however, four points of interest were found in the data. First, depression was a significant predictor of reduced leftward cradling bias. This supports the findings of previous studies that depression disrupts leftward cradling bias (Alzahrani, 2012; Scola, Arciszewski, Measelle, & Vauclair, 2013; Vauclair & Scola, 2009; Weatherill et al., 2004). Second, stress was not a statistically significant predictor of reduced leftward cradling bias. This was surprising as stress has been shown to disrupt leftward cradling bias in the literature (Alzahrani, 2012;; Reissland, Hopkins, Helms, & Williams, 2009; Suter, Huggenberger, Blumenthal, & Schachinger, 2011; Suter, Huggenberger, & Schächinger, 2007). This lack of significance was attributed to the measure of daily stress used, indicating that future research should concentrate on major life stressors. Third, depression and stress were significantly correlated with each other. Thus, future research should take into account the interaction between them. Fourth, attachment style was not a significant predictor of reduced leftward cradling bias. However, it had a statistically significant correlation with depression and stress, which are connected to disrupted leftward cradling bias. Thus, the role between depression, stress, attachment style should be further explored.